Comparative flower peduncle anatomy of three hydrophytes from the Danube Delta (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
The article comprises comparative investigation of the flower peduncle in three floating hydrophytes from the Danube Delta. The anatomical features of the peduncle structure of Nymphaea alba L., Nuphar luteum (L.) Sibth. & Sm. and Hydrocharis morsus-ranae L. are in accordance with their floating nature. Each peduncle tissue has been described and discussed, illustrations included.
Keywords: Nymphaea alba, Nuphar luteum, Hydrocharis morsus-ranae, hydrophytes, Danube Delta.